2021
DOI: 10.7759/cureus.16247
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of a Saga of Post-COVID-19 Complications

Abstract: Coronavirus disease 2019 , caused by severe acute respiratory syndrome coronavirus 2, is characterized by symptoms such as fever, sore throat, cough, fatigue, myalgias, headache, diarrhea, and dysgeusia. In a majority of the cases, it causes mild illness. However, in severe cases, the virus activates the immune system causing systemic inflammation, immune dysregulation, and pro-thrombotic state leading to various complications. Among hospitalized patients with COVID-19, pneumonia, sepsis, and respiratory failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…31 Finally, seven studies proposed long term follow up and monitoring of COVID-19 patients to enable the early detection of late multisystem manifestations. 15,34,49,62,64,77,79 Proposed further research questions by included studies. Many studies emphasized that further high-quality observational research is needed to determine the exact nature of the relationship between COVID-19 and iRMD development, with a particular focus on the mechanisms underlying any potential association.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Finally, seven studies proposed long term follow up and monitoring of COVID-19 patients to enable the early detection of late multisystem manifestations. 15,34,49,62,64,77,79 Proposed further research questions by included studies. Many studies emphasized that further high-quality observational research is needed to determine the exact nature of the relationship between COVID-19 and iRMD development, with a particular focus on the mechanisms underlying any potential association.…”
Section: Resultsmentioning
confidence: 99%
“…The exact terminology varied between studies and, for the purposes of this review, reported iRMDs have been grouped according to the ICD‐11 categories: RA, polymyalgia rheumatica and giant cell arteritis, adult‐onset Still disease, juvenile idiopathic arthritis, inflammatory spondylarthritis, SLE, systemic sclerosis, idiopathic inflammatory myopathy, vasculitis, psoriatic arthritis, direct infection of joint, and inflammatory arthropathies unspecified. In the case reports and case series, the most commonly reported iRMDs were “reactive arthropathies” (n = 47), 14,22–43 followed by “inflammatory arthropathies unspecified” (n = 18), 15,23,24,38,44–52 RA (n = 12), 53–62 and SLE (n = 11) 6,59,63–71 . The single observational (cross‐sectional) study by Taha et al reported that following an episode of COVID‐19, 37 out of 100 people observed (37%) developed “post COVID arthritis.” 72 …”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory reactive arthritis involving various joints, avascular necrosis (AVN) 112 , hemophagocytic lymphohistiocytosis (HLH) 113 (Table . 1), primary septic arthritis, glucocorticoid-induced osteonecrosis of the femoral head (GIONFH) 114,115 and softtissue abscess have been reported as a post-COVID-19 complication in many studies. Suggested causes for such complications are fat embolism, fat hypertrophy, coagulopathy, vascular endothelial dysfunction, and bone marrow stem cell abnormalities 114,116 . 12…”
Section: Musculoskeletalmentioning
confidence: 99%
“…On the following day, 23-G pars planar vitrectomy (TPPV) was performed and vitreous aspirate was taken for Gram stain and culture, Fungal culture[ 3 ] viral studies and for COVID-19 RT-PCR. [ 4 5 ] After the routine closure of 23-G TPPV, intravitreal voriconazole 100 microgram/0.1 cc was given empirically[ 3 ] and was put on topical prednisolone acetate 1% with topical moxifloxacin 6 hourly and added oral voriconazole 200 mg bd.…”
Section: Case Reportmentioning
confidence: 99%